Double diffusive natural convection of smoke in a main flow. (6th April 2005) - Kamakura, Katsuyoshi; Ozoe, Hiroyuki
The double diffusive natural convection of smoke in a horizontal main flow was numerically studied at the Prandtl number Pr = 0.71, the aspect ratio A = 1, the Rayleigh number Ra = 10 7 – 10 9, the Peclet number Pe = Re·Pr = 1000–3000, the buoyancy ratio N = 0.8 – 1.2 and the Lewis number Le = 0.5 – 5. Double diffusive phenomena with plumes occurred downstream at Ra = 10 9 . When the Peclet number is small, the smoke was extensively disordered downstream. When the Lewis number is smaller or greater than unity, the smoke was disordered downstream and separated into the thermal and solutal plumes. Then the lower side of smoke had strong plumes at Le > 1 and the upper side had strong plumes at Le < 1.